Comprehensive phytochemical profiling of Curcuma caesia Roxb. rhizome using HRLC-MS and GC-MS - Rudra, P; Darshee, B; Ramachandran, A V; Elizabeth, R (Plant Science Today, 2026)
Curcuma caesia Roxb., also called black turmeric, belonging to the Zingiberaceae family, is a rhizomatous herb and is widely known for its medicinal importance, such as for its antibacterial, anti-inflammatory and antioxidant properties. Despite its medicinal properties, the characterisation of secondary metabolites remains scarce. Total phenolic and flavonoid content were evaluated to validate the therapeutic value of the plant. This research also focuses on the profiling of the methanolic extract of C. caesia rhizomes using high-resolution liquid chromatography-mass spectrometry (HR LC-MS) and gas chromatography-mass spectrometry (GC-MS). Through the metabolite profiling, the study revealed more than 50 phytochemical compounds, including phenols, flavonoids, terpenoids, alkaloids and fatty acids. Extracts also showed elevated peak intensities, like curcumene, valine, cinnamic acid and (+)-ar-turmerone. The medicinal importance of C. caesia is highlighted by its unique phytochemicals, found via GC-MS and LC-MS analysis, which are also present in other Curcuma species as reported in the literature. These results bridge the gap between previous research studies and contemporary analytical science, suggesting the inclusion of this plant in cosmetic, nutraceutical and pharmaceutical advancements for high-value product development.